Immune challenge but not dietary restriction affects spatial learning in the wild subterranean rodent Ctenomys talarum - Schleich, Cristian (2015)
Several lines of evidence suggest that learning and triggering an immune response are both metabolically expensive and thus likely to be subject to nutritional trade-offs between them and other competing demands. Therefore, we evaluated if an immune challenge with a novel antigen affects spatial learning in the subterranean rodent Ctenomys talarum under two different dietary conditions. The results showed that immune-challenged animals were affected in their spatial learning capabilities, increasing the number of errors and marginally the time required to reach the goal of a complex labyrinth. No effect of the dietary restriction nor interaction between factors were observed. This work provides support for the existence of a trade-off between the costs of the immune defense and learning abilities, indicating that when investment is required to fight infection, fewer resources are available for learning. The absence of effect of nutritional condition on this trade-off suggests that other physiological processes, besides cognition, may be limited by the energetic resources necessary to the more immediately critical immune response.